2013
DOI: 10.1039/c3fo30309h
|View full text |Cite
|
Sign up to set email alerts
|

Milk protein hydrolysates activate 5-HT2C serotonin receptors: influence of the starting substrate and isolation of bioactive fractions

Abstract: Milk protein hydrolysates generated with different starting substrates, including sodium caseinate (NaCN), acid casein (Acid CN), skim milk powder (SMP) and glycomacropeptide (GMP) were demonstrated to behave as serotonin 2C (5-HT 2c ) receptor agonists. The 5-HT 2c receptor activating potential of NaCN hydrolysates correlated with an increased protein hydrolysis, most likely due to 10 enhanced release of bioactive peptides over the time course of hydrolysis. In its unhydrolysed form, GMP was the only starting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…[44][45][46] Furthermore, an in vitro study involving HEK293A human embryonic kidney cells transfected with two isoforms of the 5-HT 2C (serotonin) receptors, demonstrated receptor agonist activity in response to casein hydrolysate fractions suggesting casein peptides, including β-casomorphins, may be involved in the regulation of food intake and the suppression of appetite through serotonin receptors. 47 Conversely, radioreceptor analysis indicated that both human and bovine β-CM7 act as 5-HT 2C antagonists, 48 suggesting a stimulatory role for these peptides. The effect of β-Lg on satiety is also unclear, however many studies report the satiating effect of whey protein 49,50 with one recent study implicating a role for β-Lg 51 in satiety.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] Furthermore, an in vitro study involving HEK293A human embryonic kidney cells transfected with two isoforms of the 5-HT 2C (serotonin) receptors, demonstrated receptor agonist activity in response to casein hydrolysate fractions suggesting casein peptides, including β-casomorphins, may be involved in the regulation of food intake and the suppression of appetite through serotonin receptors. 47 Conversely, radioreceptor analysis indicated that both human and bovine β-CM7 act as 5-HT 2C antagonists, 48 suggesting a stimulatory role for these peptides. The effect of β-Lg on satiety is also unclear, however many studies report the satiating effect of whey protein 49,50 with one recent study implicating a role for β-Lg 51 in satiety.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, milk proteins are digested during the various stages of human GI tract digestion to give rise to an array of peptides that can elicit a variety of physiologic effects that affect the rate of digestion and transit for casein and whey proteins [ 2 , 22 , 25 , 26 ]. Some of these peptides modulate opioid [ 26 , 27 , 28 , 29 ] or serotonin receptors [ 30 ]. Whey supplementation may confer benefits for modulation of GI motility in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of -La has been shown to increase plasma W in rats 45 and in humans 50,129 , which may result in higher hypothalamic serotonin concentrations 50 . Different milk protein 60 (whey and CN-derived) hydrolysates have been shown to act as serotonin 5-HT 2C receptor agonist in embryonic kidney cell lines (HEK 293A) 131,132 . While no effect was seen in vivo with the 1 kDa permeate of a whey protein hydrolysate, the 1 kDa permeate of a CN hydrolysate was show to yield a significant reduction in 5 cumulative food intake when administered intraperiteonally (500 mg kg −1 body weight) to mice 131 .…”
Section: Satiating Properties Of W and W-containing Peptidesmentioning
confidence: 99%